Plastics technology : introduction and fundamentals - Bonten, Christian (Hanser Publishers ; Hanser Publictions, 2019)
"This introductory book covers the entire spectrum of the plastics technology/engineering, from raw material to finished plastic products. It is intended not just for university/college students but also for beginners to the field in general. The interconnectivity between the different relevant knowledge areas of plastics technology, such as materials engineering, processing technology, and product development, is emphasized. Included is a chapter "Plastics and the Environment," covering a topic (rightly) often of great concern to students and newcomers to the field. Also includes are numerous videos, conveniently linked via QR codes, to better demonstrate key processes visually"--